(untitled) (Journal of Partial Differential Equations, 2020)
Consider the blow up results for local smooth solutions of a quasilinear Schrödinger equation iu_t + Δu + β|u|^p-2u + θ(Δ|u|²)u = 0, u|_t=0 = u_0(x), x ∈ R^N in nonisotropic space.